Primary osteoporosis prophylaxis with different calcium preparations - N. V. Toroptsova; O A Nikitinskaya; L I Benevolenskaya (Научно-практическая ревматология)
Objective. To assess efficacy of different modes of management in women with osteopenia. Material and methods. 190 women with osteopenia of spine and/or femoral neck aged 50 to 70 years (mean 60,6±5 years) were followed up during a year. Different modes of prophylaxis were applied. 59 pts of group 1 received Calcium D3 Nicomed 2 tablets a day, 25 pts of group 2 - Vitrum Osteomag 2 tablets a day, 46 pts of group 3 - calcium carbonate 2500 mg/day, 60 pts of control group received recommendations about diet and physical activity. Results. 3,5% from 114 pts examined had normal 25(OH)D blood level while 23% showed deficiency of vitamin D. Mean calcium consumption with milk products was 350 mg/day. Bone mineral density (BMD) significantly increased on 1,6-1% in pts older than 60 years receiving Vitrum Osteomag and Calcium D3 Nicomed respectively while younger pts did not show such changes. BMD in pts olderthan 60 years receiving calcium carbonate increased on 0,5% but this difference was not significant. Tolerability of all 3 drugs was comparable.